(3TQM OjhGf GdMeGSI dCHi JeGes - (3CHh CMeO Ydj Hf eMeO Hf GdMSf GdeQRhbis; (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s ((3eMeO Hf CHj WGgQ Hf CHj fUQ GdCTLYi s)
(3BNQgG (B:s
(3jfJgi H` hbGd BNQ dbOeGJ HGdHjVGA ef LGfH GdMei eJi cGf RjfG ddehGcH hGdTQH s
(3fSNI NGeSI s
(3SbW ef Chdg GdOjHGLI hTQM HjJ hGMOs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs